Atypical hemolytic uremic syndrome in high-risk neuroblastoma patient: case report - A. Yu. Smirnova; Yu. V. Dinikina; A. A. Tereshina; E. P. Evsutina; M. B. Belogurova (Онкогематология)
Atypical hemolytic uremic syndrome is a rare disorder uncontrolled complement activation, which is classically manifested by anemia, thrombocytopenia and renal failure. Extrarenal manifestations are observed in 20 % of patients, most of which are associated with damage of the central nervous system. Eculizumab is effective treatment option. The article describes a case report of the severe atypical hemolytic uremic syndrome in a 20 m. o. patient who received immunotherapy with anti-GD2 antibodies (dinutuximab beta) for a high-risk neuroblastoma.